2005
DOI: 10.1299/jsmeb.48.540
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of CO2-Based Rankine Cycle Powered by Solar Energy

Abstract: An experiment study was carried out in order to investigate feasibility of CO 2 -based Rankine cycle powered by solar energy. The proposed cycle is to achieve a cogeneration of heat and power, which consists of evacuated solar tube collectors, power generating turbine, heat recovery system, and feed pump. The Rankine cycle of the system utilizes solar collectors to convert CO 2 into high-temperature supercritical state, used to drive a turbine and produce electrical power. The cycle also recovers thermal energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…In the present study, the evacuated collector described by Zhang et al (2005) was used, which is shown in Figure 2, and the details can be seen in the Reference. A simple one-dimensional model was set up to simulate the solar collector.…”
Section: Thermodynamic Analysis Of the Proposed Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the evacuated collector described by Zhang et al (2005) was used, which is shown in Figure 2, and the details can be seen in the Reference. A simple one-dimensional model was set up to simulate the solar collector.…”
Section: Thermodynamic Analysis Of the Proposed Cyclementioning
confidence: 99%
“…The measured value of 0:012 kg s À1 (Zhang et al, 2005) was used for CO 2 mass flow rate m CO 2 : January, April, July and October are selected as typical winter, spring, summer and autumn seasons, respectively, in Kyoto, Japan.…”
Section: Co 2 Cycle Performance In One Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…Its ODP (ozone depression potential) equals to 0, and GWP (global warming potential) equals to 1. It can be used widely in industry, such as working fluid in Rankine cycle [2], refrigeration cycle [3][4] and seperated heat pipe system [5][6][7]. In the heat exchanger of Rankine or refrigeration cycle, carbon dioxide is super critical fluid, so it is important to study the heat transfer character of super critical carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al investigated a thermodynamic cycle powered by solar energy for both power and heat generation using supercritical carbon dioxide as a working fluid on theoretical aspect [2][3][4], and they examined the effects of various design conditions and climate conditions on the performances of this CO 2 -based Rankine cycle. They also set up an experimental system to validate the feasibility of this supercritical carbon dioxide cycle [5][6][7][8]. Cayer et al [9] expressed a detailed analysis of a carbon dioxide trans-critical power cycle using an industrial low-grade stream of process gases as its heat source.…”
Section: Introductionmentioning
confidence: 99%